Enrichment of Limestone Used in the Desulphurisation of Fluidised-Bed-Boiler Flue Gases - Buryan Petr; Tomas Hlincik (Adsorption Science & Technology)
In this work, we analysed the impact of adding several previously untested Sorbacal calcium-based substances to the raw limestone that is currently used for dry desulphurisation of brown-coal fluidised-bed boilers. Our focus was to examine whether these additives could potentially improve the limestone SO2 adsorption capacity. The main criterion was the time period for which each enriched limestone was able to keep its desulphurisation ability, i.e., time for which the SO2 concentration in the heated model flue gas was kept below 200 mg/m3 (current legal limit for the technology in our scope). The analysis showed that the limestone desulphurisation ability increased when 20% of Sorbacal SP was added to the calcined limestone. The overall desulphurisation capacity of this enriched mass was even higher than what would be proportional to the isolated capacity of the additive itself. On the other hand, the enrichment of raw limestone with Sorbacal H 90 proved to be unpromising for the technology of brown-coal fluidised-bed boilers as the fine particles of the additive were carried away, and fluidised bed was inhomogeneous with ducts forming in it.